A Pengembangan Media Mobile Learning Berbantu Puzzle Untuk Meningkatkan Hasil Belajar IPAS Siswa: Development of Puzzle-Assisted Mobile Learning Media to Improve Student Science Learning Outcomes - Zulfa Nur'aini; Ali Sunarso (UNIB Press, 2024)
This research aimed to develop Puzzle-Assisted Mobile Learning, test the feasibility of Puzzle-Assisted Mobile Learning, and test the effectiveness of Puzzle-Assisted Mobile Learning on animal life cycle science material for class V students at SDN 2 Redin Purworejo. This research was conducted using a quantitative approach with the type of research, namely research and development (R&D). Research were conductedwith the ADDIE development model. The sampling technique uses purposive sampling technique. Data collection techniques use interviews, questionnaires, tests and documentation. Data analysis was carried out using feasibility tests and media effectiveness tests. Initial data analysis technique using normality test and final data analysis using paired t test and N-gain test. The results of the two dependent sample t test in the large group final test obtained a value of t_count = 16.929 and t_table = 2.093. From the calculation results, it is obtained that t_count = 16.929 > t_tabel = 2.093, so H0 is rejected and Ha is accepted or interpreted that the Mobile Learning Puzzle Game is effectively used in learning to improve science learning outcomes on animal life cycle material. The N-gain in the small and large group tests is 0.80 and 0.75 and is included in the high category. Researchers suggest that teachers can use Puzzle-Assisted Mobile Learning as a medium to improve students' ability to understand similar material.